2021
DOI: 10.3389/fonc.2021.784925
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis to Identify MAGEA3 Expression Correlated With Immune Infiltrates and Lymph Node Metastasis in Gastric Cancer

Abstract: Gastric cancer (GC) is an aggressive malignant tumor and causes a significant number of deaths every year. With the coming of the age of cancer immunotherapy, search for a new target in gastric cancer may benefit more advanced patients. Melanoma-associated antigen-A3 (MAGEA3), one of the members of the cancer-testis antigen (CTA) family, was considered an important part of cancer immunotherapy. We evaluate the potential role of MAGEA3 in GC through the TCGA database. The result revealed that MAGEA3 is upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Validation using different methodologies demonstrated that the risk scores based on CTARSig were STAD-independent prognostic factors with good predictive finiteness and stability. Among the 11 CTA-related genes involved in the construction of CTARSig, MAGEA3 promotes the proliferation of GC cells and chemotherapy drug resistance [21] and is associated with lymph node metastasis and immune infiltration in GC [22]. In contrast, the upregulation of MAGEA11, a member of the MAGE family, in GC has been shown to be significantly associated with lower survival rates and immune infiltration, suggesting that MAGEA11 may be a potential biomarker and therapeutic target in GC [23].…”
Section: Discussionmentioning
confidence: 99%
“…Validation using different methodologies demonstrated that the risk scores based on CTARSig were STAD-independent prognostic factors with good predictive finiteness and stability. Among the 11 CTA-related genes involved in the construction of CTARSig, MAGEA3 promotes the proliferation of GC cells and chemotherapy drug resistance [21] and is associated with lymph node metastasis and immune infiltration in GC [22]. In contrast, the upregulation of MAGEA11, a member of the MAGE family, in GC has been shown to be significantly associated with lower survival rates and immune infiltration, suggesting that MAGEA11 may be a potential biomarker and therapeutic target in GC [23].…”
Section: Discussionmentioning
confidence: 99%